2013
DOI: 10.1016/j.maturitas.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Age at natural menopause in relation to all-cause and cause-specific mortality in a follow-up study of US black women

Abstract: Objectives Early age at natural menopause has been associated with increased all-cause mortality in several studies, although the literature is not consistent. This relation has not been examined among African American women. Study design Data were from the Black Women’s Health Study, a follow-up study of African-American women enrolled in 1995. Among 11,212 women who were naturally menopausal at entry to the study or during follow-up through 2008, we assessed the relation of age at natural menopause to all-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 29 publications
0
43
0
1
Order By: Relevance
“…Age at menopause was classified into the following categories according to the literature: <40, 40-44, 45-49, 50-54, or ≥55 years. 14,15,19 Reproductive lifespan was defined as the difference between ages at menopause (natural or surgical) and menarche and categorized into quartiles (<33, 33-37, 38-40, or >40 years). Parity was defined as the number of term pregnancies.…”
Section: Methodsmentioning
confidence: 99%
“…Age at menopause was classified into the following categories according to the literature: <40, 40-44, 45-49, 50-54, or ≥55 years. 14,15,19 Reproductive lifespan was defined as the difference between ages at menopause (natural or surgical) and menarche and categorized into quartiles (<33, 33-37, 38-40, or >40 years). Parity was defined as the number of term pregnancies.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with previous research in Norway (Jacobsen, Heuch, & Kvale, 2007) and California (Jacobsen et al, 2009) that found a 2.4 and 4.5% (respectively) reduced risk of overall mortality associated with a one-year delay in onset of menarche. Many studies have also linked all-cause mortality to an early age at menopause (some studies indicate earlier than age 40, while others suggest the relationship occurs prior to age 45) (Gold, 2011; Jacobsen, Heuch, & Kvale, 2003; Li et al, 2013; Mondul et al, 2005; Ossewaarde et al, 2005; Shuster et al, 2010). Studies also have found that women who experienced menopause prior to age 40 experience mortality ranging from 35–95% higher compared with women who reported menopause occurring at age 50 years or older (Gold et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…While there is growing evidence that reproductive timing is associated with a number of specific diseases (as discussed in the sections above), some argue that early reproductive timing is a biological marker of cumulative stress (Barkow, 1984; Belsky, Steinberg, & Draper, 1991; Chisholm, Quinlivan, Petersen, & Coall, 2005) or accelerated somatic aging (Li et al, 2013; Svejme, Ahlborg, Nilsson, & Karlsson, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Early menopause has been linked with greater cardiovascular disease (CVD) risk, 13 and shown to be associated with a greater incidence of heart failure (HF), 4 coronary artery disease and stroke. 5 CVD is the leading cause of death in women 6 and early diagnosis is useful for optimization of care and improvement in therapy.…”
Section: Introductionmentioning
confidence: 99%